The principle of unitary character of the EUTM: A legal chimera? - Johansson, Alma (Stockholm Intellectual Property Law Review, 2025)
The article examines the relationship between the protection of reputation for the well-known European Union Trade Marks (EUTM) and the unitary character of the EUTM. The principle of unitary character plays an important role in enhancing the European union (EU) internal market. EUTM should therefore be given the same protection throughout the union. To obtain reputation protection, the earlier EUTM need to have a reputation in the EU and where use of that sign without due cause takes unfair advantage of, or is detrimental to, the distinctive character or the repute of the EUTM. Legal application issues arise when the principle of unitary character is to be applied together with the aforementioned requirements. The main research question addressed in the article is whether the EUTM maintains its unitary character when applying reputation protection. Given the strong connection of the question to EU law, EU law is applied to the greatest extent. Since the issue has not been addressed previously, case law from the Court of Justice of the European Union serves as the primary legal source for interpreting the meaning of the conditions for protection of reputation in the absence of other guidance. Furthermore, the impact of the unitary character in the application of reputation protection is examined. The article concludes that the unitary character of the EUTM losing its impact in the application of reputation protection.